A Neognathodus-based biozonation of the Desmoinesian Series (Pennsylvanian) in the Illinois Basin, USA. (July 2019) - Zimmerman, Alexander N.; Brown, Lewis M.; Rexroad, Carl B.
Abstract: The Neognathodus Index (NI) is developed as a primary biostratigraphic indicator for the Desmoinesian Series of the Illinois Basin in Indiana, Illinois, and Kentucky. It is based on the gradual evolutionary morphotypic variations of P1 elements of named species of Neognathodus Dunn, 1970. The NI analyses and zonations presented herein are constructed from 472 productive conodont samples from 105 different localities. NIs for the Illinois Basin show morphologic drift in Indiana from the Perth Limestone Member of the Staunton Formation (NI = 2.03) to the Velpen Limestone and Mecca Quarry Shale members of the Linton Formation (NI = 5.04) followed by stability through the Alum Cave (NI = 4.83). Further morphologic drift then occurred through the Providence Limestone Member of the Dugger Formation (NI = 5.43) and continued through the West Franklin Limestone Member of the Shelburn Formation (NI = 6.32) until the extinction of Neognathodus at the end of Desmoinesian. The patterns of drift and stability translate to Neognathodus biozones and are supported by Kolmogorov-Smirnov tests of standardized Neognathodus morphotype distributions. Localized NI variations are due to morphologic shifts and differential evolution in response to localized environmental conditions. Examination of the NI differences in the states of Illinois, Kentucky, and Indiana reflect similar morphologic simplification of the P1 element from Perth to Velpen and Mecca Quarry in Indiana (NI = 2.03–5.04) and from Seville to Brereton in Illinois and Kentucky (NI = 2.80–5.00). Post-Brereton in Illinois and Kentucky (NI = 5.00–5.65) and post-Providence in Indiana (NI = 5.43–6.32) saw progressive P1 simplification, but it was much more pronounced in Indiana.